Proximate Composition and Phytochemical Analysis of Six Minor Fruits of Bangladesh (Bangladesh Journal of Botany, 2023)
Nutritional composition of six minor fruits of Bangladesh namely, Annona reticulata L., Manilkara zapota (L.) P.Royen, Aegle marmelos (L.) Corrêa, Diospyros malabarica (Desr.) Kostel., Averrhoa carambola L. and Garcinia pedunculata Roxb. ex Buch-Ham. were studied. Dry matter, ash, crude fat, crude protein, crude fibre and crude carbohydrate contents largely varied among the studied fruits. All fruits exhibited the presence of alkaloids, flavonoids, terpenoids, tannins, phenols, and saponins. At premature stage, total phenolics and tannin contents varied from 14.59 to 1.32 and from 9.76 to 0.29 (mg GAE g–1 DW), respectively while at mature stage, these ranged from 9.82 to 0.87 and from 5.98 to 0.23. At premature and ripening stages, the maximum chlorophyll content was detected in A. reticulata and M. zapota, respectively. Based on the calorific value, Garcinia pedunculata performed better followed by M. zapota, and A. carambola the least among the studied fruits; although, A. reticulata possesses the largest amount of crude protein and crude fibre.Bangladesh J. Bot. 52(1): 111-118, 2023 (March)